A Renewable Light‐Promoted Flexible Li‐CO2 Battery with Ultrahigh Energy Efficiency of 97.9 - Wang, Xiao‐Xue; Guan, De‐Hui; Li, Fei; Li, Ma‐Lin; Zheng, Li‐Jun; Xu, Ji‐Jing (Small (Weinheim an der Bergstrasse, Germany), 2021)
Directly converting and storing abundant solar energy in next‐generation energy storage devices is of central importance to build a sustainable society. Herein, a new prototype of a light‐promoted rechargeable and flexible Li‐CO2 battery with a TiO2/carbon cloth (CC) cathode is reported for the direct utilization of solar energy to promote the kinetics of the carbon dioxide reduction reaction and carbon dioxide evolution reaction (CO2ER). Under illumination, photoelectrons are generated in the conduction band of TiO2/CC, followed by the enhancing diffusion of electrons and lithium ions during the discharge process. The photoelectrons on the cathode surface can regulate the morphology of the discharge product Li2CO3, contributing to boosting the kinetics of the subsequent CO2ER process. In the reverse charge process, photogenerated holes can favor the decomposition of Li2CO3, leading to a negative charge potential of 2.88 V without increased polarization over ≈60 h of cycling. Owing to an ultralow overpotential of 0.06 V between the discharge and charge process, an ultrahigh energy efficiency of 97.9% is attained under illumination. The introduction of a light‐promoted flexible Li‐CO2 battery can pave the way toward developing the use of solar energy to address the charging overpotential of conventional Li‐CO2 batteries. A renewable light‐promoted flexible Li‐CO2 battery is developed inspired by the photoenergy conversion and utilization concept. The utilization of solar light can effectively alleviate the charge polarization and promote the Li+ diffusion and mass transfer, resulting in considerable improvement of the kinetics of the carbon dioxide reduction reaction and carbon dioxide evolution reaction processes in the Li‐CO2 battery.